Guillain Barré syndrome associated to dengue in a hospital in Peru: a case report - Ordinola-Calle, Deysi Daniela (2025)
Guillain-Barré syndrome is a disabling immunologically mediated disease associated with multiple triggering agents. The dengue outbreak in Perú peaked in the second half of May 2023. The presentation of neurological complications, including immune-mediated complications, has a wide variability in its clinical manifestations and is considered a severe presentation of dengue. We present the case of a 69-year-old male patient with Guillain-Barré syndrome and positive serology for the nonstructural viral protein 1 (NS1) antigen for dengue without warning signs, who 10 days after the onset of symptoms went to the emergency room for ascending flaccid quadriparesis that in the electrodiagnostic study was classified as acute sensory-motor axonal neuropathy (AMSAN) with favorable evolution after treatment with plasma exchange.